Analisa Proses Produksi dan Aplikasi Minyak Pirolisis Kulit Jambu Mete Sebagai Bahan Bakar Alternatif - Ato, La; Mangalla, Lukas Kano; Samhuddin, Samhuddin (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2019)
Energy is a basic human need, which continues to increase. Fossil fuels are one of the limited fuels. The purpose of the study is the analysis of the production process and application of cashew skin oil pyrolysis as an alternative fuel. A variation in the size of the material to obtain a liquid product pyrolysis results and perform testing pyrolysis results with the flame test. Pyrolysis carried out at a temperature of 300-400 oC. Performed pyrolysis with some variation in the size of the material, namely coarse, medium and smooth. The results of the study showed the higher the pyrolysis temperature the more liquid product mass-produced. Cashew seed skin pyrolysis by using ordinary water-cooling media produces 210 ml of liquid product, ICE cooler produces a liquid product of 225 ml and use the air-cooling medium by 160 ml. Second variation using skin Cashew nut medium with ordinary water pending media of liquid generated at 170 ml, ice water 165 ml and air 172 ml. The third variation of using cashew skin smoothly with regular water cooling produces a fluid of 217 ml, ES 220 and air 167 ml. Conducted research on the analysis of the production process and application of cashew skin oil pyrolysis as an alternative fuel.Keywords: energy, cashew skin, and pyrolysis